Association of Epoxide Hydrolase 2 Gene Arg287Gln with the Risk for Primary Hypertension in Chinese - Liang Ma; Hailing Zhao; Meijie Yu; Yumin Wen; Tingting Zhao; Meihua Yan; Qian Liu; Yongwei Jiang; Yongtong Cao; Ping Li; Wenquan Niu (International Journal of Hypertension)
Background. Epoxide hydrolase 2 (EPHX2) gene coding for soluble epoxide hydrolase is a potential candidate in the pathogenesis of hypertension. Objectives. We aimed to assess the association of a missense mutation, R287Q, in EPHX2 gene with primary hypertension risk and examine its association with enzyme activity of soluble epoxide hydrolase. Methods. This study involved 782 patients with primary hypertension and 458 healthy controls. Genotyping was done using TaqMan technique. Activity of soluble epoxide hydrolase fusion proteins was evaluated by the conversion of 11,12-EET to corresponding 11,12-DHET using ELISA kit. Results. After taking carriers of R287Q variant GG genotype as a reference, those with GA genotype had a significantly reduced risk of hypertension (adjusted odds ratio: 0.72, 95% confidence interval: 0.56 to 0.93, P = 0.013). Five significant risk factors were identified, including age, body mass index, total cholesterol, homocysteine, and R287Q variant. These five risk factors for hypertension were represented in a nomogram, with a descent prediction accuracy (C-index: 0.833, P<0.001). Enzyme activity of soluble epoxide hydrolase was significantly lower in the R287Q group than in the wild type group. Conclusions. We provide evidence that R287Q mutation in EPHX2 gene was associated with reduced risk of primary hypertension and low activity of soluble epoxide hydrolase.